Erlotinib-loaded carboxymethyl temarind gum semi-interpenetrating nanocomposites. (15th February 2020) - Bera, Hriday; Abbasi, Yasir Faraz; Lee Ping, Law; Marbaniang, Daphisha; Mazumder, Bhaskar; Kumar, Pramod; Tambe, Prajakta; Gajbhiye, Virendra; Cun, Dongmei; Yang, Mingshi
Graphical abstract: Highlights: CMTG-g-PNIPA-MMT based semi-IPN NCs was synthesized. It depicted excellent biodegradability and pH/temperature-dependent swelling. ERL was loaded via probe sonication-assisted self-assembly protocol. Formulation F-3 exhibited highest DEE with sustained drug release at 8 h. It efficiently suppressed A549 cell proliferation and promoted apoptosis. Abstract: Erlotinib-loaded carboxymethyl temarind gum- g -poly(N-isopropylacrylamide)-montmorillonite based semi-IPN nanocomposites were synthesized and characterized for their in vitro performances for lung cancer therapy. The placebo matrices exhibited outstanding biodegradability and pH-dependent swelling profiles. The molar mass ( M ¯ c) between the crosslinks of these composites was declined with temperature. The solid state characterization confirmed the semi-IPN architecture of these scaffolds. The corresponding drug-loaded formulations displayed excellent drug-trapping capacity (DEE, 86–97 %) with acceptable zeta potential (−16 to −13 mV) and diameter (967−646 nm). These formulations conferred sustained drug elution profiles (Q8h, 77–99 %) with an initial burst release. The drug release profile of the optimized formulation (F-3) was best fitted in the first order kinetic model with Fickian diffusion driven mechanism. The mucin adsorption to F-3 followed Langmuir isotherms. The results of MTT assay, AO/EB staining and confocal analyses revealed that the ERL-loaded formulation suppressed A549 cell proliferation and induced apoptosis more effectively than pristine drug.